Causes of Uncertainties in Paleoclimatic Reconstructions Based on the Oxygen Isotope Composition of Glacier Ice on Elbrus (Western Plateau) - Ju. Chizhova N.; V. Mikhalenko N.; S. Kutuzov S.; I. Lavrentiev I.; V. Lipenkov Ya.; A. Kozachek V.; Ю. Чижова Н.; В. Михаленко Н.; С. Кутузов С.; И. Лаврентьев И.; В. Липенков Я.; А. Козачек В. (IGRAS, 2024)
A study of the isotope signature of glacial ice in the Western Elbrus Plateau (the Caucasus) was made on the basis of five ice cores obtained in different years with high resolution. It was shown that the isotopic characteristics of ice are associated with the processes of accumulation and wind scouring of snow. Three ice cores were obtained in 2013 (C–1, C–2 and C–3), one in 2017 (C–4) and one more in 2018 (C–5). Core sampling was performed with a resolution of 5 cm. Isotopic analysis was done at the CERL laboratory (AARI) using a Picarro L2130-i isotope analyzer, the accuracy was 0.06‰ for δ18O and 0.30‰ for δ2Н. The values of d18О and δ2Н of the ice of the Western Plateau generally vary from –5 to –30‰ and from –18.7 to –225.8‰, respectively, with well-defined seasonality. Comparison of the isotope record for all cores showed that the differences in accumulation for individual seasons reach 0.3 m w. eq., differences in accumulation for individual seasons averaged over 5 years is approximately 0.2 m w.eq. The absolute differences in the average seasonal values of d associated with wind scouring and spatial redistribution of snow (deposition noise), averaged over 5 years, reached 1.38‰. The irregularity of precipitation amount within the season and errors in core dating are an additional contribution to non-climate variance (noise of definition). The absolute difference in the average seasonal values of δ18O associated with this type of noise averaged over 5 years is 1.7‰. Thus, the total uncertainty for two different types of noise can be estimated at 2.2‰, which is about 20% of the annual seasonal amplitude of δ18O values of the glacier ice in the Western Plateau (the average difference between the δ18O values of warm and cold seasons is ~10–11‰). One of the problems of linking the isotope record to the annual temperature record at the weather station was solved by using ammonium concentrations for dating the C-1 ice core and calculating the “ide+al” annual variation of δ18O values by a cosine function of the ...